Duetting as a Collective Behavior - Logue, David M.; Krupp, Daniel Brian (Frontiers in Ecology and Evolution, 2016)
Mated birds of many species vocalize together, producing duets. Duetting behavior occurs at two levels of organization: the individual level and the pair level. Individuals initiate vocalizations, answer their mates' vocalizations, and control the structure and timing of their own vocalizations. Pairs produce duets that vary with respect to duration, temporal coordination, and phrase-type combinations, among other properties. To make sense of this hierarchical structure, organize duetting research, and identify new avenues of investigation, we advocate a “collective behavior” approach to the study of duets. We critically review key terminology in the duetting literature in light of this approach, and elucidate six insights that emerge from the collective behavior approach: (1) Individual-level behaviors describe pair-level behaviors, but the opposite is not true; (2) The level of organization informs how we test for the rules that govern behavior; (3) Functional hypotheses about duetting must distinguish individual from group characters; (4) Stimulus-response, cybernetics, and entrainment offer alternative hypotheses for the cognitive control of duetting behavior; (5) Avian duetting has the potential to be a model system for the ontogeny of vocal interaction; and (6) The collective behavior approach suggests new avenues of research. Ultimately, we argue that nearly every aspect of duetting research stands to benefit from adopting a collective behavior approach. This approach also has applications to other forms of interactive vocal communication in birds and primates, including humans.